2019
DOI: 10.1371/journal.pone.0220423
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting type-specific seasonal influenza after 26 weeks in the United States using influenza activities in other countries

Abstract: To identify countries that have seasonal patterns similar to the time series of influenza surveillance data in the United States and other countries, and to forecast the 2018–2019 seasonal influenza outbreak in the U.S., we collected the surveillance data of 164 countries using the FluNet database, search queries from Google Trends, and temperature from 2010 to 2018. Data for influenza-like illness (ILI) in the U.S. were collected from the Fluview database. We identified the time lag between two time-series wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In this study, total INF in Argentina showed a high correlation with ILI after 30 weeks in South Korea. In our previous study, total INF in Australia and Chile showed a high correlation with ILI after 22 and 28 weeks, respectively, in the United States [ 7 ]. Countries in the southern hemisphere showed different influenza patterns, and we identified those with seasonal patterns and influenza outbreaks similar to but preceding those of the reference country [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, total INF in Argentina showed a high correlation with ILI after 30 weeks in South Korea. In our previous study, total INF in Australia and Chile showed a high correlation with ILI after 22 and 28 weeks, respectively, in the United States [ 7 ]. Countries in the southern hemisphere showed different influenza patterns, and we identified those with seasonal patterns and influenza outbreaks similar to but preceding those of the reference country [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Missing data were replaced with a zero. Total influenza (INF) was defined as the sum of the number of influenza A and B viruses detected among processed specimens [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used in studies about infectious diseases, mental health, general diseases, public behavior and its seasonality. [7][8][9][10][11] . CC-BY-NC-ND 4.0 International license It is made available under a perpetuity.…”
Section: Introductionmentioning
confidence: 99%